Spring drought variability in Yunnan within Southwest China from 1580s to 2020s and its impacts on social unrest - Qian Li; Yinxian Shi; Zhenhua Li; Bin Liu; Hua Huang; Xuefei Yang; Jianchu Xu; Yingfeng Bi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mg hydrogen generator based intelligent responsive stent for in situ therapy of reflux esophagitis - Guokai Zeng; Junjie Liang; Yuxuan Zhang; Guofeng Zeng; Xiaoying Li; Qiansha Luo; Bingjun Wu; Yuxin Tang; Jiazheng Chen; Shuhan Zhou; Fang Qin; Qi He; et al. (Chemical Engineering Journal, 2026)

Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Multifunctional carbon nanowebs for solar-driven desalination and water purification with integrated Photothermal, antibacterial, and adsorptive capabilities - Bing Gao; Zhi Liu; Soon Huat Tan; Jianghui Zhao; Yingfeng Wang; Siew Chun Low (Desalination, 2026)

Long-term exposure to ultrafine particles accelerates biological aging and increases respiratory vulnerability in COPD - Yingfeng Gao; Xin Meng; Yi Zhang; Qiaoyi Hua; Ruiwei Xu; Huixia Liu; Seokho Choi; Haoyang Yao; Qianli Dong; Qi Jia; Haixia Jiang; Lijuan Wei; et al. (Journal of Hazardous Materials, 2025)

Prediction of critical volatile organic compounds and identification of flavor intensity in Gastrodia elata under different preparation methods based on NIR and FTIR feature variables - Yingfeng Zhong; Jieqing Li; Honggao Liu; Yuanzhong Wang (Food Research International, 2025)

Tanshinone IIA ameliorates pancreatic injury in type 2 diabetic mice by modulating inflammation and endoplasmic reticulum stress via the IL-6/JAK2/STAT3 pathway - Yingfeng Li; Desheng Wang; Yuhang Liu; Chenyang Liu; Meixi Chen; Jingqi Li; Zunqiu Wu; Ning Wu (Functional & Integrative Genomics, 2025)

What is the relationship between urban heat island (UHI) effect and urban surface parameter (USP) at micro-scale? A case study in Gulangyu, China - Yuan Li; Yingfeng Wang; Mengsheng Yang; Yanan Du; Jingge Liu (Sustainable Cities and Society, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Balance between strength and toughness for fully bio-based composites achieved by oriented design of filler - Kang Chen; Ruixia Liu; Ce Sun; Dingyuan Zheng; Yuanyuan Miao; Yingfeng Zuo; Haiyan Tan; Yanhua Zhang (Chemical Engineering Journal, 2025)

Spatio-Temporal Dynamics of Particulate Organic Carbon and Its Response to Climate Change: Evidence of the East China Sea from 2003 to 2022 - Zhenghan Liu; Yingfeng Chen; Xiaofeng Lin; Wei Yang (Journal of Marine Science and Engineering, 2025)
Particulate organic carbon (POC) plays a crucial role in oceanic climate change. However, existing research is limited by several factors, including the scarcity of long-term data, extensive datasets, and a comprehensive understanding of POC dynamics. This study utilizes monthly average POC remote sensing data from the MODIS/AQUA satellite to analyze the spatiotemporal variations of POC in the East China Sea from 2003 to 2022. Employing correlation analysis, spatial autocorrelation models, and the Geodetector model, we explore responses to key influencing factors such as climatic elements. The results indicate that POC concentrations are higher in the western nearshore areas and lower in the eastern offshore regions of the East China Sea (ECS). Additionally, concentrations are observed to be lower in southern regions compared to northern ones. From 2003 to 2022, POC concentrations exhibited a fluctuating downward trend with an average annual concentration of 121.05 ± 4.57 mg/m3. Seasonally, monthly average POC concentrations ranged from 105.48 mg/m3 to 158.36 mg/m3; notably higher concentrations were recorded during spring while summer showed comparatively lower levels. Specifically, POC concentrations peaked in April before rapidly declining from May to June—reaching a minimum—and then gradually increasing again from June through December. Correlation analysis revealed significant influences on POC levels by particulate inorganic carbon (PIC), sea surface temperature (SST), chlorophyll (Chl), and photosynthetically active radiation (PAR). The Geodetector model further elucidated that these factors vary in their impact: Chl was identified as having the strongest influence (q = 0.84), followed by PIC (q = 0.75) and SST (q = 0.64) as primary influencing factors; PAR was recognized as a secondary factor with q = 0.30. This study provides new insights into marine carbon cycling dynamics within the context of climate change.

Evaluating the impacts of drilling and extraction activities on the marine carbonate system in the natural gas fields of Beibu Gulf, Northern South China Sea - Minxia Zhang; Wei Yang; Jianhang Zhang; Chuqian Lu; Yingxu Wu; Peiqiang Zhuang; Yanmei Liu; Shasha Qi; Xing Chen; Wei Deng; Zijia Zheng; Ming He; et al. (Marine Environmental Research, 2025)

Large-scale interviews and plot-based data reveal declining yields of the prized matsutake mushrooms in the major producing areas of China - Yingfeng Bi; Bin Liu; Guangli Chen; Ti Bu; Pengwan Zhang; Qinghong Zhou; Liqin Mu; Yao Fu; Yinxian Shi; Xuefei Yang; Deli Zhai (Journal of Environmental Management, 2025)

Effect of (−)-epigallocatechin gallate palmitate complexation under mild temperature on the structure and nutritional functions of porous rice starch - Hai He; Qi He; Yugang Zhang; Jia Sun; Yingfeng Tu; Hongwei Wang; Fang Qin; Kun Liu (Food Chemistry, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

How to classify microclimates more validly and finely? A novel method for mapping local climate zone (LCZ) on micro-scales - Mengsheng Yang; Yuan Li; Yanan Du; Yingfeng Wang; Jingge Liu; Lijuan Yang; Jingxiong Huang (Sustainable Cities and Society, 2025)

High slab thermal gradient facilitates dehydration and megathrust ruptures in the Solomon Sea plate - Weiling Zhu; Yingfeng Ji; Lijun Liu; Rui Qu; Ye Zhu (Journal of Asian Earth Sciences, 2025)

Application of opposing coils transient electromagnetic method in urban area with metal interference - Juan Fan; Enke Hou; Dewu Jin; Zhenzhu Xi; Xia Long; Sheng Zhou; Shenghui Nan; Yingfeng Liu; Kang Guo; Dianyan Ning (Journal of Applied Geophysics, 2024)

Industry 4.0 and cleaner production: A comprehensive review of sustainable and intelligent manufacturing for energy-intensive manufacturing industries - Shuaiyin Ma; Wei Ding; Yang Liu; Yingfeng Zhang; Shan Ren; Xianguang Kong; Jiewu Leng (Journal of Cleaner Production, 2024)

Study on the thermal effect of coal oxidation under different stresses - Jiangkun Chao; Shuang Liu; Rongkun Pan; YingFeng Yuan; Daimin Hu (Science of The Total Environment, 2024)

Large language models for diabetes care: Potentials and prospects - Bin Sheng; Zhouyu Guan; Lee-Ling Lim; Zehua Jiang; Nestoras Mathioudakis; Jiajia Li; Ruhan Liu; Yuqian Bao; Yong Mong Bee; Ya-Xing Wang; Yingfeng Zheng; Gavin Siew Wei Tan; et al. (Science Bulletin, 2024)

Helical hydrogel micromotors for delivery of neural stem cells and restoration of neural connectivity - Suyi Liu; Bin Chen; Ye Feng; Chao Gao; Dailing Du; Tingting Jiang; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2024)

High-zeta-potential accelerates interface charge transfer in lithium anodes via MXene-graphdiyne heterojunction layers - Lu Sun; Meifeng Li; Jianan Gu; Yingfeng Li; Jinzhang Liu; Yan Li; Meicheng Li (Chemical Engineering Journal, 2023)

Light-driven micromotor swarm induced in-situ polymerization and synergistic photothermal therapy - Zeqi Li; Shaoming Fu; Huaan Li; Bin Chen; Dazhi Xie; Dongmei Fu; Ye Feng; Chao Gao; Suyi Liu; Daniela A. Wilson; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2023)

Flexural behavior of damaged RC beams strengthened with prestressed UHPC layer - Yang Zhang; Songling Huang; Yingfeng Liu; Wei Fan; Xudong Shao (Engineering Structures, 2023)

Study on failure characteristics and in situ stress inversion of brittle shale under complex loading - Houbin Liu; Shuai Cui; Yingfeng Meng; Jiajun Wang; Bin Lv (Arabian Journal of Geosciences, 2022)

Nano- to micro-pore characterization by synchrotron radiation SAXS and nano-CT for bituminous coals - Yixin Zhao; Chujian Han; Yingfeng Sun; Nima Noraei Danesh; Tong Liu; Yirui Gao (Frontiers of Earth Science, 2021)

A new method for wellbore stability evaluation based on fractured carbonate reservoir rock breaking degree - Houbin Liu; Shuai Cui; Yingfeng Meng; Xu Han; Teng Liu; Yu Fan; Ye Tao; Anran Yu (Arabian Journal of Geosciences, 2021)

PK15 cell line stably overexpressing IL2 enhances PCV2 replication - Xuliang Zhang; Yingfeng Zhao; Chang Ma; Jinwei You; Min Dong; Shifeng Yun; Jie Liu (Virus Genes, 2021)

Multi-coupling stress field and evaluation of borehole stability in deep brittle shale - Teng Liu; Houbin Liu; Yingfeng Meng; Xu Han; Shuai Cui; Anran Yu (Arabian Journal of Geosciences, 2020)

Influence of relation between stress field and bedding space on wellbore stability in shale formation - Houbin Liu; Shuai Cui; Yingfeng Meng; Xiangyang Zhao; Xu Han (Arabian Journal of Geosciences, 2019)

Dynamic analysis of wellbore stress field and wellbore stability in carbonate reservoir production process - Houbin Liu; Shuai Cui; Yingfeng Meng; Xu Han (Arabian Journal of Geosciences, 2019)

An experimental study on stress sensitivity of tight sandstone gas reservoirs during nitrogen drilling - Meng Yingfeng; Luo Chengbo; Li Gao; Liu Houbin (Arabian Journal of Geosciences, 2019)

A method suitable for DNA extraction from humus-rich soil - Tianjin Miao; Song Gao; Shengwei Jiang; Guoshi Kan; Pengju Liu; Xianming Wu; Yingfeng An; Shuo Yao (Biotechnology Letters, 2014)